Millennium Development Goals (MDG) Gap Task Force Report 2010 - United Nations (United Nations, 2013)
Much progress has been made since 2000, but there is still a great deal more to be achieved in order to fulfill the promise of the Millennium Development Goals (MDGs). In this sense, the global partnership for development stands at a critical juncture, with only five years left until the 2015 deadline to delivery on the commitments made and to achieve the MDGs. Remaining gaps are still very large and there have been setbacks because of the global food, energy and financial crises. The deadline for commitments in a number of crucial areas (including increased aid volume, improved aid effectiveness, and the conclusion of the Doha Round of trade negotiations) is 2010, but there is little prospect of successful delivery. The report identifies the implementation gaps in the commitments made under MDG 8 and provides recommendations on how to address them, on strengthening the global partnership, and achieving the MDGs.